Elevated Serum Human Epididymis Protein 4 Is Associated With Disease Activity and Systemic Involvements in Primary Sjögren’s Syndrome - Chen, Jiali; Sun, Feng; Bao, Huizhang; Liang, Liu; Zhan, Minghua; Yao, Haihong; He, Jing; Liu, Yudong (Frontiers in Immunology, 2021)
Background We aimed to investigate the clinical utility of human epididymis protein 4, a tumor biomarker being widely utilized in clinical practice in the diagnosis of ovarian cancer, in primary Sjögren’s Syndrome (pSS). Methods A total of 109 pSS patients and 113 healthy controls (HCs) were included in the study. HE4 were determined by Roche Cobas E601 electrochemical luminescence analyzer. Clinical and laboratory findings were reviewed, and the relationships between HE4 and clinical parameters were determined by Spearman’s correlation test. The European league against rheumatism Sjögren’s syndrome disease activity index (ESSDAI) was utilized to evaluate disease activity. Findings The levels of HE4 were significantly elevated in patients with pSS compared to HCs (103.65 pmol/L vs. 46.52 pmol/L, p<0.001). The levels of HE4 were positively correlated with ESSDAI scores (r=0.462, p<0.001). Significant positive correlations between the levels of HE4 with pulmonary involvements (r=0.442, p<0.001) and renal involvements (r=0.320, p=0.001) were observed. Receiver operating curve (ROC) analysis revealed an optimal cut-off value of 104.90 pmol/L and 128.05 pmol/L for distinguishing patients with pulmonary and renal involvements, with the areas under the ROC curve (AUCs) of 0.778 (95%CI 0.685-0.870, p<0.001) and 0.768 (95%CI 0.646-0.891, p=0.001), respectively. Among patients with pulmonary involvement, the levels of HE4 were positively correlated with the semiquantitative HRCT grade (r=0.417, p=0.016), and negatively correlated with the percentage of forced vital capacity (FVC) (r= -0.460, p=0.047) and diffusing capacity of the lung for carbon monoxide (DLco) (r= -0.623, p=0.004). For patients with renal involvement, HE4 was positively correlated with creatinine (r=0.588, p=0.021) and negatively correlated with estimated glomerular filtration rate (r= -0.599, p=0.030). Conclusions Our findings demonstrated a novel role of HE4 in clinical stratification of pSS, suggesting that introducing HE4 to the current pSS test panel may provide additional diagnostic value, particularly in evaluating disease activity and pulmonary/renal involvements.